tell me the answer fasttt i will give them 20 points if u tell with process no spams
Attachments:
![](https://hi-static.z-dn.net/files/d68/7c66334aa906b811bc1cee2272ba134d.jpg)
gbannu1234p9xzq9:
pro
Answers
Answered by
2
the answer is option D
Attachments:
![](https://hi-static.z-dn.net/files/d63/44e6c6fe3329235a118cc8ef053457dc.jpg)
Answered by
0
x⁴+x²+1
=x⁴+x²+1
=x⁴+2x²-x²+1 [∵ x²=2x²-x²]
=(x⁴+2x²+1)-x²
={(x²)²+2×x²×1+(1)²}-(x)²
=(x²+1)²-(x)²[∵ a²+2ab+b²=(a+b)²]
=(x²+1+x)(x²+1-x)[∵a²-b²=(a+b)(a-b)]
=(x²+x+1)(x²-x+1)
∴the factors of x⁴+x²+1 are (x²+x+1)&(x²-x+1).
∴option(3)is correct.
=x⁴+x²+1
=x⁴+2x²-x²+1 [∵ x²=2x²-x²]
=(x⁴+2x²+1)-x²
={(x²)²+2×x²×1+(1)²}-(x)²
=(x²+1)²-(x)²[∵ a²+2ab+b²=(a+b)²]
=(x²+1+x)(x²+1-x)[∵a²-b²=(a+b)(a-b)]
=(x²+x+1)(x²-x+1)
∴the factors of x⁴+x²+1 are (x²+x+1)&(x²-x+1).
∴option(3)is correct.
Similar questions